Cultural Adaptation and Integration of the Vietnamese Community in Australia - Nguyen, Tri Minh (Resolusi: Jurnal Sosial Politik, 2023)
The Vietnamese community in Australia has faced numerous challenges during its integration into Australian society. Starting with language barriers and cultural differences, the community has had to navigate a complex set of social, economic, and political factors to establish its position in the country. Despite these obstacles, they have maintained their cultural identity while embracing the Australian way of life. One of the most significant contributions of the Vietnamese community to Australian society has been their ability to bring about fresh perspectives and opportunities for cultural exchange. The younger generations of Vietnamese Australians, in particular, have been instrumental in highlighting the values of inclusivity and multiculturalism. They have been at the forefront of promoting cultural diversity and understanding and acceptance of different communities. Our research aims to systematically document the adaptation and integration of the Vietnamese community in Australia across different periods. We employ qualitative methods to analyse the various factors that have contributed to the success of the Vietnamese community in Australia. By doing so, we hope to provide a comprehensive understanding of the challenges and opportunities faced by the Vietnamese community during their integration into Australian society.